Intergeracionalidade das práticas de disciplina parentais: fatores que mantêm e fatores que quebram esse ciclo - Sarmento, Raquel Salvadori (Universidade Federal de São Carlos, 2019)
Disciplinary behaviors and the way to educate children tend to be passed on from generation to generation, in which individuals reproduce with their children the behaviors that their parents emitted in their education. The present study aimed to verify the variables related to the intergenerational nature of parental discipline practices. To achieve this goal, the study was divided into two moments: an online survey data collection and the realization of a focus group. The survey was attended by 35 parents (29 mothers and 6 fathers) of children aged 3-6 years (20 girls and 15 boys), recruited from two early childhood schools and social networks. The participants answered an online form in which there were questions related to the characterization of the participants, about the discipline practices received in the childhood of the participants and those they applied in their children's education (Discipline Dimension Inventory - Retrospective Version and Parents Version, respectively), and a questionnaire prepared by the author based on the literature in the area to identify variables related to the maintenance / disruption of intergenerationality. The results indicated a statistically significant correlation between some disciplinary practices used by the participant's mother and father and the practices used by them in their children's education. The majority (77.1%) of the participants answered that they never, almost never or sometimes repeated with their children the parenting practices that their parents used in their childhood. Participants who responded that they do not maintain the intergenerational cycle attributed this break mainly to access to information (69.2%) and negative assessment of parenting (30.8%). The participants who replied that they maintained the intergenerational cycle attributed this mainly to the positive evaluation of the parents' parenting (75%), followed by the influence of the partner and the same socioeconomic level (both with 37.5%). The focus group participants were recruited from an invitation made available at the end of the form used in the survey.Of the 35 participants, 9 responded to the invitation and two mothers participated in the focus group, which took place in a meeting lasting approximately one hour. In the focus group, trigger videos were presented to encourage discussion on the topic and, at the end, some data from the literature were taken. Both participants had 2 children and reported having difficulties with the discipline of their first child, seeking professional help from psychologists to access positive parenting discipline information. In addition to professional help, both considered that the support of the partner and the negative evaluation of the practices used by their parents during their childhood contributed to the disruption of the intergenerational cycle of parenting practices. Thus, it is possible to verify a congruence between the quantitative data obtained from the instruments and qualitative data from the focus group, indicating that the disruption of intergenerationality occurs due to access to information, assistance from the partner and negative evaluation of the discipline practices used by parents. The study proved to be limited due to the reduced number of participants and sociodemographic characteristics (high schooling and income). Future studies with a larger number of participants and with more diversity in relation to socioeconomic level and education, in order to bring about a greater generalization and understanding regarding the variables that contribute to the maintenance / disruption of intergenerationality.
Intergenerational parenting practices: factors that maintain and factors that break this cycle
Keywords: Intergeracionalidade; Práticas de disciplina parentais; Criança; Intergenerationality; Parental behavior pratices; CIENCIAS HUMANAS::PSICOLOGIA::TRATAMENTO E PREVENCAO PSICOLOGICA